Green Practices with Renewable Distributed Generation Technology in India - Kumar M.; Samuel C. (My University, 2025)
In the modern electricity sector, power industries are facing the challenge to meet exponentially growing electricity demand with the constraint of reducing carbon emission. Overcoming these issues, the power sector is getting motivated to use decentralized renewable energy based renewable distributed generation (RDG) technology to meet growing demand and reduce carbon emission to meet the government environmental regulations and social equality. The role of management and small size generating units are playing as the key factor in the adoption of green RDG practices. In this work, authors identified factors influencing power sector to adopt green RDG practices through a survey in Indian power industries. After analysis of survey data, the role of government regulation as the most important factor in choosing environment friendly practices has been identified. A significant relationship has been shown between government regulations and managerial concern for using green RDG practices with apparent stakeholder pressures. Findings show that effect of factors influencing green RDG environmental regulation is significant. This analysis will help in the decision-making process to increase concern over green RDG practices. © 2018 Walter de Gruyter GmbH, Berlin/Boston.